Hospice Care Legislation in South Korea and Its Implications for China - Lanqiu LIU, Yue ZHAO (Zhongguo quanke yixue, 2022)
The Act on Decisions on Life-sustaining Treatment for Patients in Hospice and Palliative Care or at the End of Life (hereinafter referred to as the Hospice Care Act) enacted by South Korea in 2016, clearly defines the definition of hospice care and the premise of implementing hospice care, stipulates the hospice care responsibilities and liabilities for the country's government, and sets up the framework of the hospice care system, which is of great significance to promote the development of hospice care and to protect the rights and interests of passing away peacefully in end-of-life patients in South Korea. We introduced the main contents of the Hospice Care Act, and the achievements obtained in South Korea since its implementation, aiming at providing insights into the promotion of hospice care legislation in China. To provide an all-round and refined legal protection for hospice care reform, innovation and high-quality development in China to support healthy dying in end-of-life patients, we put forward the following recommendations: clarifying the rights for hospice care patients, enacting specific regulations on hospice care when conditions are ripe, building a government-led hospice care system, affirming the concept of ineffective medical treatment, and stipulating the process of utilization of hospice care.